Therapeutic Effects of Tryptanthrin and Tryptanthrin-6-Oxime in Models of Rheumatoid Arthritis - Kirpotina, Liliya N.; Schepetkin, Igor A.; Hammaker, Deepa; Kuhs, Amanda; Khlebnikov, Andrei I.; Quinn, Mark T. (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic destructive autoimmune disorder characterized by joint and bone destruction that is mediated in part by proteases and cytokines produced by synovial macrophages and FLS. Although current biological therapeutic strategies for RA have been effective in many cases, new classes of therapeutics are needed. Here, we investigated the anti-inflammatory effects of plant-derived alkaloid tryptanthrin (Trp) and its synthetic derivative tryptanthrin-6-oxime (Trp-Ox). Both Trp and Trp-Ox inhibited matrix metalloproteinase (MMP)-3 expression in interleukin (IL)-1β-stimulated primary human fibroblast-like synoviocytes (FLS), IL-1β-stimulated secretion of MMP-1/3 in synovial SW-982 cells, and production of IL-6 in human umbilical vein endothelial cells (HUVECs), SW-982 cells, and monocytic THP-1 cells, although Trp-Ox was much more effective. Evaluation of the therapeutic potential of Trp and Trp-Ox in murine arthritis models showed that both compounds significantly attenuated development of collagen-induced arthritis (CIA) and collagen-antibody-induced arthritis (CAIA), with Trp-Ox again being the most effective. Collagen II (CII)-specific antibody levels were reduced in Trp- and Trp-Ox-treated in CIA mice. Trp and Trp-Ox suppressed proinflammatory cytokine production by lymph node cells, with Trp-Ox being more effective in inhibiting IL-17A, granulocyte-macrophage colony-stimulating factor (GM-CSF), and receptor activator of nuclear factor-κB ligand (RANKL). While both Trp and Trp-Ox were both effective in inhibiting RA, Trp-Ox was the most effective, which is likely due to its ability to inhibit c-Jun N-terminal kinase (JNK), which is not a target of Trp. Overall, Trp-Ox may represent a potential new direction for pursuit of novel treatments for RA.